Economic comparison of naked vs. conventional oat in Finland - Kirkkari, Anna-Maija (MTT, 2004)
In Finland oat, almost purely conventional oat, has been the second-most cultivated grain after barley in recent decades. Despite naked oats excellent nutritional value, cultivation of naked oat has failed to spread in Finland, partially because of generally outdated concepts according to which naked oat suffer from low yield and reduced germination and seedling emergence. Production cost calculations conducted by different advisory organisations show that the cultivation of oat, conventional or naked, in Finland is more cost-effective than that of barley and wheat. This is mainly because of need for lower variable costs caused by disease control, liming and fertilisation. Two thirds of Finnish oat production is directly consumed on farms as livestock feed. In the feed use of grain, the value is based on energy values, nutritional values and digestibility. In terms of energy yield, wheat and naked oat exceed barley. But the hectare-based energy yield of dehulled conventional oat is lower than that of barley aswell owing to the significant loss during dehulling (20%). In terms of nutritive value, naked oat is a competitive cereal even if the yield was moderate. An economic study accommodating the feed values and yield levels of naked oat proves that naked oat is a competitive alternative for oat, dehulled oat and barley. For pigs and poultry, naked oat is also more economical than wheat in the Finnish conditions. When comparing conventional oat with naked oat, it is necessary to consider the higher processing costs caused by the hulls of conventional oat in various phases of production. Information centre of the ministry of agriculture and forestry 2000. Yearbook of Farm Statistics 2000. Helsinki 266 p; Valentine, J. 1990. Aspects of Applied Biology 25: 19-27; Welch, R. W. 1995. In: Welch R.W. (ed.), The Oat Crop, pp. 279-320, Chapman & Hall, London, UK.
Keywords: Ka; naked oat; cost; energy value; economic; production; feed